(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Anwar K, Putra RA, Karni I, Kurniawan A, Amalyadi R, Unsunnidhal L, Kisworo D, Ali M. 2025. Screening and characterization of lactic acid bacteria from the gastrointestinal tract of a native chicken (Gallus gallus f. domesticus) as probiotics. Biodiversitas 26: 2653-2661. Probiotic bacteria have been reported to confer beneficial effects on poultry health and performance. Nevertheless, probiotic strains derived from Indonesian native chickens are not widely available, restricting the application of appropriate probiotic strains as an alternative substitution for antibiotic growth promoters in the poultry industry. In the present study, we aimed to screen, identify, and characterize Lactic Acid Bacteria (LAB) strains from the gastrointestinal tract of a native chicken (Gallus gallus f. domesticus). A native chicken was purchased from an officially approved slaughterhouse. The gastrointestinal tracts, including the small intestine and cecum, were gathered aseptically and used for bacterial isolation. A total of three LAB isolates were obtained and subjected to initial screening according to the morphological, biochemical, and molecular analyses. Two selected isolates (LC12 and LC16) demonstrating Gram-positive, rod-shaped, catalase-negative, and non-motile characteristics were tested under simulated gastrointestinal conditions to reveal potential probiotic characteristics, followed by amplifying and sequencing the 16S rRNA gene. The results demonstrated that two selected isolates had high survival rates, greater than 90% at pH 7.2 and 55% at pH 2.0 after 2-hour and 4-hour incubation, respectively, suggesting adaptability over a wide range of pH conditions. Both isolates indicated tolerance to 0.3% bile salt with a survival rate of more than 70%. Molecular identification using partial-length 16S rRNA sequences showed that the isolates LC12 and LC16 were genetically identified as Lactobacillus johnsonii strain 6-3 with a similarity of 100% for both isolates. The selected LAB isolates are promising probiotic candidates for favorable applications in the poultry industry.